Interdependent durations in joint retirement - Bo E. Honoré; Áureo de Paula (Centre for Microdata Methods and Practice (cemmap), 2013)
In this paper we specify and use a new duration model to study joint retirement in married couples using the Health and Retirement Study. Whereas conventionally used models cannot account for joint retirement, our model admits joint retirement with positive probability, allows for simultaneity and nests the traditional proportional hazards model. In contrast to other statistical models for simultaneous durations, it is based on Nash bargaining and it is therefore interpretable in terms of economic behavior. We provide a discussion of relevant identifying variation and estimate our model using indirect inference. The main empirical finding is that the simultaneity seems economically important. In our prefered specification the indirect utility associated with being retired increases by approximately 10% if one's spouse is already retired. By comparison, a defined benefit pension plan increases indirect utility by 20-30%. The estimated model also predicts that the indirect effect of a change in husbands' pension plan on wives' retirement dates is about 10% of the direct effect on the husbands.
Keywords: J26; C41; C3; 330